2016 10th European Conference on Antennas and Propagation (EuCAP) 2016
DOI: 10.1109/eucap.2016.7481609
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor-to-indoor path loss modeling at 10.1 GHz

Abstract: This paper presents a grazing angle dependent outdoor-to-indoor (O2I) path loss model at 10.1 GHz for a glass and a concrete wall. The COST 231 O2I path loss model is used as a baseline in model creation. The parameters for the model are derived from radio channel measurements performed with a vector network analyzer and a single-input single-output antenna configuration at 500 MHz bandwidth. The results indicate that attenuation through the concrete wall is heavily dependent on the wall material whereas the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(7 reference statements)
0
1
0
1
Order By: Relevance
“…Knowledge of the propagation loss characteristics in the outdoor-to-indoor (O2I) environment is important for this purpose. To clarify the building entry loss (BEL) characteristics, radio propagation measurements were conducted by up to the 2 GHz band [2,3], 3.5 GHz band [4], 5 GHz band [5,6], 8 GHz band [7], 10 GHz band [8], and 38 GHz band [9]. It was confirmed that the BEL characteristics changed according to the incident angle of the radio wave to the building.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the propagation loss characteristics in the outdoor-to-indoor (O2I) environment is important for this purpose. To clarify the building entry loss (BEL) characteristics, radio propagation measurements were conducted by up to the 2 GHz band [2,3], 3.5 GHz band [4], 5 GHz band [5,6], 8 GHz band [7], 10 GHz band [8], and 38 GHz band [9]. It was confirmed that the BEL characteristics changed according to the incident angle of the radio wave to the building.…”
Section: Introductionmentioning
confidence: 99%
“…Em [9] estuda-se os efeitos que o corpo humano pode causar à uma rede indoor na faixa de frequência de 10 GHz, considerando o corpo humano em movimento. Em [10] é descrito um modelo de perda de percurso para uma frequência centrada em 10,1 GHz, analisando os efeitos que uma janela de vidro e uma parede de concreto podem gerar em uma situação em que o transmissor está em um ambiente outdoor e o receptor está em um indoor.…”
unclassified